MIXED-SPICES SUPPLEMENTATION SUPPRESSES FAT DEPOSITION AND CAUSES NO ALTERATIONS IN LIPID AND RED BLOOD CELL PROFILES IN BROILER CHICKENS - Idoko, A. S.; Zaharaddeen, A. S.; Ilouno, E. I.; Nura, L.; Sabiu, U. A.; Alao, S. O.; Idoko, I.; Saidu, M. (FUDMA JOURNAL OF SCIENCES, 2023)
This research was conducted to determine the carcass traits, lipid and red blood cell indices of broiler chickens fed mixed spices-supplemented diet. Driedand pulverized spices; Allumsativum (garlic), Zingiberofficinale (ginger) and Punicagranatum (pomegranate) were mixed in ratio of 2:2:1 respectively.The mixed-spices were combined with Starter and Finisher to formulate four (4) diets; A was non-supplemented Starter, B was 2% mixed spices-supplemented Starter, C wasnon-supplemented Finisher and D was 2% mixed spices-supplemented Finisher. In the first phase of the experiment, 150 chicks were divided into groups 1 and 2 of 75 birds each, and randomly assigned to diets A and B. Groups 1and 2were respectively maintained on diets A and B for 3 weeks. In the second phase, group 1 in the first phase was sub-divided into groups A and B while group 2 was sub-divided into groups C and D and fed ad libitum for additional 3 weeks. The feed intake, carcass traits, lipid and red blood cell indices were determined. Increase in weight and feed intake were significantly lower (p<0.05) in the birds fed 2% mixed spices supplemented Starter. All the test groups had significantly lower (p<0.5) percentage fat to carcass weight as compared to the control (A). Other evaluated carcass traits did not vary significantly (p>0.5). All evaluated red blood cell indices, lipid and artherogenic indices did not significantly differ (p>0.5) from the control. Conclusively, the spices could suppress fat accumulation in broiler chicken, without affecting other carcass traits, lipid and red blood cell indices